The association between prune belly syndrome and dental anomalies: a case report - Basso, Maria Daniela; Favretto, Carla Oliveira [UNESP]; Cunha, Robson Frederico [UNESP] (Biomed Central Ltd., 2012)
Background: Prune belly syndrome is a rare condition produced by an early mesodermal defect that causes abdominal abnormalities. However, the literature indicates that disturbances related to ectodermal development may also be present. This is the first case report in the literature to suggest that dental abnormalities are part of the broad spectrum of clinical features of prune belly syndrome. Because the syndrome causes many serious medical problems, early diagnosis of abnormalities involving the primary and permanent dentitions are encouraged.Case presentation: The authors report the clinical case of a 4-year-old Caucasian boy with prune belly syndrome. In addition to the triad of abdominal muscle deficiency, abnormalities of the gastrointestinal and urinary tracts, and cryptorchidism, a geminated mandibular right central incisor, agenesis of a mandibular permanent left incisor, and congenitally missing primary teeth (namely, the mandibular right and left lateral incisors) were noted.Conclusion: This original case report about prune belly syndrome highlights the possibility that dental abnormalities are a part of the broad spectrum of clinical features of the syndrome. Therefore, an accurate intra-oral clinical examination and radiographic evaluation are required for patients with this syndrome in order to provide an early diagnosis of abnormalities involving the primary and permanent dentitions.
Keywords: Prune belly syndrome; Tooth abnormalities; Child